Binderless tungsten carbide carbon control with pressureless sintering. (November 2018) - Fox, R.T.; Nilsson, R.
Abstract: Binderless tungsten carbide material systems can achieve properties which make them ideal for use within highly abrasive wear environments, though carbon control is essential for reaching maximum density and performance levels when sintered in the absence of applied pressure. Introducing WO3 and W additives coupled with controlled thermal processing cycles provides a means to moderate the excess carbon introduced coincident with greenware forming methods required for practical shaping. With sintering temperatures of 1700 °C, controlled final stoichiometry and hardnesses up to 2700 kg/mm 2 are demonstrated. Highlights: A means to control excess carbon utilizing additives during pressureless processing of binderless WC systems is developed. Specific levels of W, WO3, and their impact on carbon content, density, and resultant hardnesses are described. Practical utility is demonstrated using the high organic loadings necessary for complex greenware shaping. Densification at 1700 deg. C and controlled grain growth result in measured hardnesses up to 2700 kg/mm 2 .